Association between environmental stress factors, salivary cortisol level and dental caries in Egyptian preschool children: a case-control study - Yosra Ahmed Hussein; Rania Hussein Refai; Mai M. K. Hussein; Mamdouh Hanafy Abdou; Magdy Mohamed El Bordini; Ola Mohamed Ewais; Mohamed Fakhry Hussein (Scientific Reports)
Abstract Dental caries remains the most common chronic disease in childhood. This study aimed to identify environmental stressors in children and estimate the association between salivary cortisol level as a stress biomarker and childhood caries. We conducted a case-control study involving 80 Egyptian children. The cases were 40 children with early childhood caries (ECC). The controls included 40 caries-free children. Data were collected from the parents or caregivers of the children using a questionnaire. The clinical examination included caries experience and an oral hygiene index. Saliva samples were collected and tested for unbounded cortisol levels. The results from the current study showed that the mean age for participants was 5.09 ± 0.66 years. Twenty-one of the children with ECC were girls. In multivariate regression, there is a significant association between ECC and elevated salivary cortisol levels (> 0.57 µg/dl) with an adjusted odds ratio (AOR) of 9.649 (p = 0.003), father smoking (AOR = 5.791, p = 0.030), sleeping with a bottle or food in the mouth (AOR = 8.481, p = 0.027), and poor oral hygiene evaluated through the Silness-Löe Plaque Index (AOR = 6.681, p = 0.001). As a conclusion, the study indicates that salivary cortisol is an independent stress biomarker in relation to early childhood caries. Salivary cortisol as a stress biomarker can help clinicians provide an additional assessment tool for identifying caries risk in children.